2017
DOI: 10.1590/1807-1929/agriambi.v21n3p156-162
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid as attenuator of drought stress on germination and initial development of sesame

Abstract: A B S T R A C TSesame is an important crop in Northeast Brazil, where climate conditions require adapted genotypes and alternatives for plant defense against drought. This study aimed to evaluate the salicylic acid as drought attenuator in sesame genotypes. The experiment evaluated six genotypes (BRS Seda, CNPA-G2, CNPA-G3, CNPA-G4, LAG-Branquinha and LAGPretinha), five osmotic potentials (0, -0.2, -0.4, -0.6 and -0.8 MPa) and three seed treatments (soaking in distilled water, in salicylic acid and no treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…In barley plants, salinity stress caused alterations in the rate of photosynthesis and membrane stability; however, these negative effects of salinity stress were ameliorated by the application of SA ( Janda et al, 2012 ). Similar observations were reported by da Silva et al (2017) in case of SA at 10 -5 M which increased plant growth of sesame under drought stress ( da Silva et al, 2017 ). The treatment of maize with SA reduced the accumulation of Na in plant tissue and mitigated salt-induced negative effects on plants ( Gunes et al, 2007 ).…”
Section: Role Of Phytohormones In Plant Response To Abiotic Stresssupporting
confidence: 88%
See 2 more Smart Citations
“…In barley plants, salinity stress caused alterations in the rate of photosynthesis and membrane stability; however, these negative effects of salinity stress were ameliorated by the application of SA ( Janda et al, 2012 ). Similar observations were reported by da Silva et al (2017) in case of SA at 10 -5 M which increased plant growth of sesame under drought stress ( da Silva et al, 2017 ). The treatment of maize with SA reduced the accumulation of Na in plant tissue and mitigated salt-induced negative effects on plants ( Gunes et al, 2007 ).…”
Section: Role Of Phytohormones In Plant Response To Abiotic Stresssupporting
confidence: 88%
“…Salicylic acid is another important phytohormone with a phenolic nature, and it has an important function in plant stress tolerance through modulation of antioxidative enzyme activities ( Ahmad et al, 2011 ; da Silva et al, 2017 ). The alleviation of various abiotic stresses by application of SA was reported by Senaratna et al (2000) for water stress, by Azooz et al (2011) for salt stress and by Ahmad et al (2011) for heavy metal stress.…”
Section: Role Of Phytohormones In Plant Response To Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kadioglu et al (2011), salicylic acid acts as a signaler in the modulation of responses to environmental stresses. Silva et al (2017), evaluating the influence of salicylic acid on sesame germination under water stress, found that the use of 10 µM in seed treatment promoted greater tolerance during the initial development under water stress conditions, due to the action of the acid on the antioxidant system of the tissues.…”
Section: Cmentioning
confidence: 99%
“…Plants have developed many strategies to maintain growth when water availability is restricted or inconsistent (Silva et al, 2016), such as ionic homeostasis and activation of the enzyme antioxidant system, to promote cell detoxification and growth regulation (Zhu, 2001;Silva et al, 2017). However, these responses are generally more pronounced in genotypes that are tolerant to water deficit.…”
Section: Introductionmentioning
confidence: 99%